Notes on Public Relations practices on the web - Barichello, Eugenia Maria Mariano da Rocha; Stasiak, Daiana (Organicom, 2009)
This work presents research results that had the purpose of classifying different phases of Public Relations practices on the web (WebRP), in the course of the last fourteen years. The methodology uses the multiple cases study, where the core was developed from twelve sites studied at three different moments: the 1990s, the beginning of the 2000 decade and present time (2008/2009). At the end of the analyses we found the pertinent strategies for each period, which enabled categorization of the three WebRP phases.